2020
DOI: 10.1017/sjp.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Self-rated Health in Adolescents: The Relationships between them and the Role of Gender and Age

Abstract: The purpose of this study was to analyze the relationships between self-reported life satisfaction, self-rated health, gender, and age in adolescents. 1,141 secondary school students aged between 12 and 17 participated in our study. The data were analyzed using bivariate and nonlinear canonical correlation analyses. The results of the bivariate correlation analysis support the results of previous studies. Life satisfaction was positively correlated with same-day perceived health (r = .37; p < .01) and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Indeed, this is what the current study exactly found. The strong positive link between SRH and life satisfaction is consistent with several previous studies across countries and age groups [e.g., ( 26 , 27 )]. Indeed, good health or subjective perceived good health certainly contributes to one's overall life satisfaction as health is one of the factors that make up overall life satisfaction ( 30 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, this is what the current study exactly found. The strong positive link between SRH and life satisfaction is consistent with several previous studies across countries and age groups [e.g., ( 26 , 27 )]. Indeed, good health or subjective perceived good health certainly contributes to one's overall life satisfaction as health is one of the factors that make up overall life satisfaction ( 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, there are strong positive links between life satisfaction and SRH across countries and age groups [e.g., ( 26 , 27 )]. Indeed, good health is obviously one of the most important things to people and is often used as a source for people to evaluate overall life satisfaction ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mixed results have been reported regarding gender differences in the levels of life satisfaction and subjective well-being ( Dinisman and Ben-Arieh, 2016 ). Some studies indicate that there are no differences in the levels of well-being associated with gender, while others state that in general are more likely to show lower levels of well-being and life satisfaction ( Atienza-González et al., 2020 ; Kaye-Tzadok et al., 2017 ). These differences have been shown to be more marked as adolescence progresses ( Aymerich et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction with primary healthcare services appears to affect depression (Kavalniene et al, 2018 ). Numerous research has demonstrated a negative correlation between life satisfaction and depression (Gómez-Restrepo et al, 2013 ; Atienza-González et al, 2020 ; Köttl et al, 2021 ). However, the relationship between institutional satisfaction and depression among hypertension patients in elderly caring SOs remains unknown.…”
Section: Introductionmentioning
confidence: 99%